1985
DOI: 10.1007/bf01871650
|View full text |Cite
|
Sign up to set email alerts
|

Spin probe clustering in human erythrocyte ghosts

Abstract: A model has been developed for 5-nitroxide stearate, I(12,3), distribution in human erythrocyte ghosts which accurately predicts ESR spectral alterations observed with increased probe/total lipid (P/L) at 37 degrees C. This spin probe occupies a class of high-affinity, noninteracting sites at low loading. Saturation occurs with increasing probe concentration, and, at higher loading, the probe inserts itself at initially dilute sites to form membrane-bound clusters of variable size. No 'low' probe remains at hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
1

Year Published

1987
1987
2004
2004

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 36 publications
1
25
1
Order By: Relevance
“…Cu 2ϩ spectra were collected at 110 K from samples contained in 4-mm inner diameter "Suprasil" quartz EPR tubes (Wilmad). Labeled lipid samples (25 l) were contained in 0.8-mm inner diameter quartz capillaries (Wilmad) and handled as described by Gordon et al (35) to ensure reproducibility. Other procedures, including adding to the spin-labeled LUV a small amount of the water-soluble, non-membrane-penetrant spin probe Tempo choline chloride to ensure x axis reproducibility, have been described previously (22,36,37).…”
Section: Methodsmentioning
confidence: 99%
“…Cu 2ϩ spectra were collected at 110 K from samples contained in 4-mm inner diameter "Suprasil" quartz EPR tubes (Wilmad). Labeled lipid samples (25 l) were contained in 0.8-mm inner diameter quartz capillaries (Wilmad) and handled as described by Gordon et al (35) to ensure reproducibility. Other procedures, including adding to the spin-labeled LUV a small amount of the water-soluble, non-membrane-penetrant spin probe Tempo choline chloride to ensure x axis reproducibility, have been described previously (22,36,37).…”
Section: Methodsmentioning
confidence: 99%
“…Spectra were recorded with a Varian E-109 ESR spectrometer fitted with a Deltron (Sydney, Australia) model DCM 20 temperature-control accessory, digitized with a Hewlett-Packard 7470A plotter and 9816 computer, and stored on floppy disc for data manipulations (16). Probe/total lipid (P/L) ratios were calculated from double integration of ESR spectra (16). A with the extremes indicating that the probe samples, respectively, fluid and immobilized environments.…”
mentioning
confidence: 99%
“…HIV (9 mg of protein per ml) was spin-labeled as described for human erythrocytes (16). Spectra were recorded with a Varian E-109 ESR spectrometer fitted with a Deltron (Sydney, Australia) model DCM 20 temperature-control accessory, digitized with a Hewlett-Packard 7470A plotter and 9816 computer, and stored on floppy disc for data manipulations (16). Probe/total lipid (P/L) ratios were calculated from double integration of ESR spectra (16).…”
mentioning
confidence: 99%
“…Previous studies have shown that nitroxide radical interactions occurred in a range of biological membranes labeled with the 5-nitroxide stearate, I(12,3) 1, spin probe (for review, see [10,17]). Above minimum probe/lipid (P/L) ratios (which may be as t Abbreviations used: 1 (12,3), the N-oxyl-4',4'-dimethyloxazolidine derivative of 5'-ketostearic acid; I (5,10), the N-oxyl-4',4'-dimethyloxazolidine derivative of 12'-ketostearic acid; ESR, electron spin resonance; P/L, ratio of probe molecules to total lipid molecules; HIV, Human Immunodeficiency Virus; AIDS, acquired immunodeficiency syndrome; S, polarity-corrected order parameter; S(TI), polarity-uncorrected order parameter; S(Ta), polarity-uncorrected order parameter; a}, isotropic hyperfine coupling constant (gauss); K., association constant for high-affinity binding sites (mg lipid/M); N, number of high-affinity binding sites (sites/mg lipid).…”
Section: Introductionmentioning
confidence: 99%
“…Above minimum probe/lipid (P/L) ratios (which may be as t Abbreviations used: 1 (12,3), the N-oxyl-4',4'-dimethyloxazolidine derivative of 5'-ketostearic acid; I (5,10), the N-oxyl-4',4'-dimethyloxazolidine derivative of 12'-ketostearic acid; ESR, electron spin resonance; P/L, ratio of probe molecules to total lipid molecules; HIV, Human Immunodeficiency Virus; AIDS, acquired immunodeficiency syndrome; S, polarity-corrected order parameter; S(TI), polarity-uncorrected order parameter; S(Ta), polarity-uncorrected order parameter; a}, isotropic hyperfine coupling constant (gauss); K., association constant for high-affinity binding sites (mg lipid/M); N, number of high-affinity binding sites (sites/mg lipid). low as 1/2500), probe concentration effects similarly broaden the ESR spectra and perturb the order parameters and polarity of such diverse I(12,3)-labeled membranes as human erythrocyte ghosts [17,19], rat liver plasma membranes [20], human platelet plasma membranes [20], human iymphocytes [11,12], and the lipid envelope of the Human Immunodeficiency Virus (HIV) responsible for the AIDS pandemic [1,16].…”
Section: Introductionmentioning
confidence: 99%